Novel dithiocarbamate derivatives are effective copper-dependent antimicrobials against Streptococcal species - Menghani, Sanjay V.; Sanchez-Rosario, Yamil; Pok, Chansorena; Liu, Renshuai; Gao, Feng; O’Brien, Henrik; Neubert, Miranda J.; Ochoa, Klariza; Durckel, Meredythe; Hellinger, Riley D.; Hackett, Nadia; Wang, Wei; et al. (Frontiers in Microbiology, 2023)
Despite the availability of several vaccines against multiple disease-causing strains of Streptococcus pneumoniae, the rise of antimicrobial resistance and pneumococcal disease caused by strains not covered by the vaccine creates a need for developing novel antimicrobial strategies. N,N-dimethyldithiocarbamate (DMDC) was found to be a potent copper-dependent antimicrobial against several pathogens, including S. pneumoniae. Here, DMDCs efficacy against Streptococcal pathogens Streptococcus pyogenes, Streptococcus agalactiae, and Streptococcus anginosus was tested using bactericidal and inductively coupled plasma - optical emission spectrometry. After confirming DMDC as broad-spectrum streptococcal antimicrobial, DMDC was derivatized into five compounds. The derivatives’ effectiveness as copper chelators using DsRed2 and as copper-dependent antimicrobials against S. pneumoniae TIGR4 and tested in bactericidal and animal models. Two compounds, sodium N-benzyl-N-methyldithiocarbamate and sodium N-allyl-N-methyldithiocarbamate (herein “Compound 3” and “Compound 4”), were effective against TIGR4 and further, D39 and ATCC® 6303™ _(a type 3 capsular strain). Both Compound 3 and 4 increased the pneumococcal internal concentrations of copper to the same previously reported levels as with DMDC and copper treatment. However, in an in vivo murine pneumonia model, Compound 3, but not Compound 4, was effective in significantly decreasing the bacterial burden in the blood and lungs of S. pneumoniae-infected mice. These derivatives also had detrimental effects on the other streptococcal species. Collectively, derivatizing DMDC holds promise as potent bactericidal antibiotics against relevant streptococcal pathogens.